SPECIFIC CHARACTERISTICS OF ADMINISTRATION IN DEVELOPED COUNTRIES - Рустамова, Сайёра (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article reveals the nature of international management styles, the specific characteristics of interpersonal relationships in different countries. It talks about the art of influencing people in the developed countries of the world, organizational culture, specific features of management in developed countries.